PERAN MUSYAWARAH DALAM MEWUJUDKAN KOMUNIKASI INTERPESONAL (STUDI ANALISIS TERHADAP HADIST TENTANG MUSYAWARAH) - Mawaddah Nurul Fitri (LP2M Universitas Islam Ahmad Dahlan Sinjai, 2025)
This research explores the importance of communication and deliberation as key instruments in social problem-solving, emphasizing their role in fostering effective and solutive interactional communication. Deliberation, as a process of exchanging opinions aimed at reaching a decision that benefits all parties, has strong roots in Islamic teachings and principles of social ethics. This research underscores that deliberation is not simply a discussion, but rather a collaborative process in which individuals exchange ideas, negotiate solutions, and attempt to reach a mutually beneficial consensus. The methodology used in this study includes a literature review of relevant hadiths as well as related scholarly articles, focusing on the principles of interactive communication and social dynamics in the context of deliberation. The main findings show that effective communication plays a crucial role in ensuring the productivity of deliberation, which in turn contributes to improved social relations and collective problem-solving capabilities. This research also emphasizes the importance of mutual respect, understanding in every discussion, as well as the role of feedback in creating constructive two-way communication channels. Overall, this research aims to provide deep insights into how deliberation can serve as an effective tool in achieving common goals and resolving conflicts in a constructive and harmonious manner.